IEEE access : practical innovations, open solutions - Abbott, Derek; Institute of Electrical and Electronics Engineers (Institute of Electrical and Electronics Engineers, 2013)
A multidisciplinary, applications-oriented, all-electronic archival journal that continuously presents the results of original research or development across all of IEEE's fields of interest. Supported by article processing charges, its hallmarks are a rapid peer review and publication process with open access to all readers.
Keywords: Technology : Periodicals; Engineering : Periodicals; Engineering; Technology